Is Silver Diamine Fluoride Effective in Arresting Enamel Caries? A Randomized Clinical Trial - Araya Phonghanyudh; Duangporn Duangthip; Sirinan Mabangkhru; Varangkanar Jirarattanasopha (My University, 2022)
Background: There is limited information on the effectiveness of 38% silver diamine fluoride (SDF) in managing enamel caries. Objective: This study aimed to compare effectiveness of 38% SDF and 5% Sodium fluoride (NaF) varnish in arresting enamel caries in young children when applied semiannually over 18 months. Methods: A randomized controlled trial was conducted on children aged 1–3 years who had at least one active carious surface. They were allocated into two groups: Group 1 (38% SDF) and Group 2 (5% NaF varnish). Visual-tactile examination was used to assess extent of carious lesions. Enamel caries that did not progress to dentin were classified as having caries arrest. Intention-to-treat analysis was performed. Results: At baseline, 290 children with 1974 tooth surfaces with enamel caries were recruited. Caries arrest rates at the tooth surface level in Group 1 and Group 2 were 59.1% and 58.8%, respectively (p = 0.873), at 18 months. The multilevel logistic regression analysis revealed that tooth position, tooth surface, extent of enamel caries at baseline, caries experience, and brushing with fluoride toothpaste influenced caries arrest (p < 0.05). Conclusion: The semiannual application of 38% SDF and 5% NaF varnish had comparable effectiveness in arresting enamel caries in primary teeth.
Keywords: Dental Erosion and Treatment